2011
DOI: 10.1107/s1600536811021131
|View full text |Cite
|
Sign up to set email alerts
|

Opipramol

Abstract: In the title compound (systematic name: 2-{4-[3-(5H-dibenz[b,f]azepin-5-yl)prop­yl]piperazin-1-yl}ethanol), C23H29N3O, the 5H-dibenz[b,f]azepine and piperazine rings adopt boat and chair conformations, respectively, and the overall shape of the fused ring part of the molecule is a butterfly. In the crystal, O—H⋯N and C—H⋯O hydrogen bonds link the mol­ecules into a layer parallel to the bc plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…However, it has pronounced D2-, 5-HT2-, and H1-blocking potential and high affinity to sigma receptors (sigma-1 and sigma-2). The crystal structure studies of opipramol dipicrate (Jasinski et al, 2010) and opipramol (Fun et al, 2011) have been reported. In view of the importance of opipramol, the paper reports the crystal structure of the title compound, (I).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has pronounced D2-, 5-HT2-, and H1-blocking potential and high affinity to sigma receptors (sigma-1 and sigma-2). The crystal structure studies of opipramol dipicrate (Jasinski et al, 2010) and opipramol (Fun et al, 2011) have been reported. In view of the importance of opipramol, the paper reports the crystal structure of the title compound, (I).…”
Section: Methodsmentioning
confidence: 99%
“…For the use of opipramol in the treatment of anxiety disorders, see: Moller et al (2001). For related structures, see: Fun et al (2011); Jasinski et al (2010). For standard bond lengths, see Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…For applications of opipramol, see: Moller et al (2001). For related structures, see: Jasinski et al (2010); Fun et al (2011); Siddegowda, Butcher et al (2011); Siddegowda, Jasinski et al (2011); Swamy et al (2007). For graph-set analysis of hydrogen bonds, see: Etter et al (1990); Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…However, it has pronounced D2-, 5-HT2-, and H1-blocking potential and high affinity to sigma receptors (sigma-1 and sigma-2). The crystal structures of opipramol dipicrate (Jasinski et al, 2010), opipramol (Fun et al, 2011), opipramolium fumarate (Siddegowda, Butcher et al, 2011) and flupentixol dihydrochloride (Siddegowda, Jasinski et al, 2011) have been reported recently. In view of the importance of the title compound we herein report its molecular and crystal structure.…”
Section: S1 Commentmentioning
confidence: 99%
“…It acts also as moderate dopamine D2, serotonin 5-HT2 and histamine H1 receptors antagonist and shows low anticholinergic activity. Opipramol has an anxiolytic, sedative and mood-improving effect, while it has less antidepressant properties [ 20 , 21 , 22 ]. When applied in the evening, it has sleep-improving effect [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%